The Routledge history of literature in English Britain and Ireland - Carter, Ronald 1947-2018; McRae, John 1949- (Routledge, Taylor & Francis Group, 2021)
"The Routledge History of Literature in English covers the main developments in the history of British and Irish literature from AD 600 to the present day. Accompanying language notes explore the interrelationships between language and literature, emphasising the growth of literary writing, its traditions, conventions and changing characteristics. Extensive quotations from poetry, prose and drama underpin the narrative. With a new chapter on novels, drama and poetry in the 21st century and an extensive companion website, The Routledge History of Literature in English will be an invaluable reference for any student of English literature and language."...